Biological potential of Bacillus subtilis BS45 to inhibit the growth of Fusarium graminearum through oxidative damage and perturbing related protein synthesis - Lu, Ziyun; Chen, Meiling; Long, Xinyi; Yang, Huilin; Zhu, Du (Frontiers in Microbiology, 2023)
Fusarium root rot (FRR) caused by Fusarium graminearum poses a threat to global food security. Biological control is a promising control strategy for FRR. In this study, antagonistic bacteria were obtained using an in-vitro dual culture bioassay with F. graminearum. Molecular identification of the bacteria based on the 16S rDNA gene and whole genome revealed that the species belonged to the genus Bacillus. We evaluated the strain BS45 for its mechanism against phytopathogenic fungi and its biocontrol potential against FRR caused by F. graminearum. A methanol extract of BS45 caused swelling of the hyphal cells and the inhibition of conidial germination. The cell membrane was damaged and the macromolecular material leaked out of cells. In addition, the mycelial reactive oxygen species level increased, mitochondrial membrane potential decreased, oxidative stress-related gene expression level increased and oxygen-scavenging enzyme activity changed. In conclusion, the methanol extract of BS45 induced hyphal cell death through oxidative damage. A transcriptome analysis showed that differentially expressed genes were significantly enriched in ribosome function and various amino acid transport pathways, and the protein contents in cells were affected by the methanol extract of BS45, indicating that it interfered with mycelial protein synthesis. In terms of biocontrol capacity, the biomass of wheat seedlings treated with the bacteria increased, and strain BS45 significantly inhibited the incidence of FRR disease in greenhouse tests. Therefore, strain BS45 and its metabolites are promising candidates for the biological control of F. graminearum and its related root rot diseases.